GEOGRAPHIC VARIABILITY IN THE DECLINE OF THE INCIDENCE OF FATAL AND NON-FATAL STROKE. (June 2018) - Kostis, J.; Zinonos, S.; Cabrera, J.; Kostis, W.
Abstract : Objective: To examine whether the decline in incidence of fatal and non-fatal stroke is affected by characteristics of the population in different geographic areas. Design and method: County specific data from the 21 counties in the state of New Jersey were obtained from the Robert Wood Johnson Foundation County Health Rankings. The percentage of the population in each county with the following medical and socioeconomic risk factors was used in the analysis: persons under the age of 18, persons 65 years or older, female, smokers, physically inactive, obese, with diabetes, diabetic monitoring among diabetics, excessive drinking, college education, median household income, unemployed, uninsured, single parent household, areas with violent crime. The counties were lumped into 4 categories based on similarities of the above characteristics. The incidence in fatal and non-fatal stroke was compared among the 4 county clusters. Results: Overall, the incidence of fatal and non-fatal stroke declined throughout the state. The incidence was significantly lower (p < 0.05) in cluster 1. There was no difference in the decline among the other 3 clusters (Figure). Compared to clusters 2, 3 and 4 in the aggregate, persons included in cluster 1 had higher household income, were more likely to have college education, and were less likely to be unemployed, to live in single parent households, to have diabetes, to be obese, to smoke, or to be physically inactive. Conclusions: The incidence of fatal and non-fatal stroke was more pronounced among persons who had better risk factor profile and higher socioeconomic status. There were no significant effects of demographics (e.g. age, gender). Figure. No caption available.